Dismantling the Exclusivity of Minimum Work Experience in Recruitment: A Deconstruction and Rawlsian Critique - Afrinda Herawati; Haekal Pradifa Furqon (Universitas Medan Area, 2026)
This study aims to critically review the exclusivity of the 'minimum work experience' criterion in labor recruitment, which is commonly regarded as a reasonable and objective primary requirement. The analysis is conducted through the philosophical perspectives of deconstruction, as elaborated by Jacques Derrida, and the Rawlsian theory of justice. The method employed is a qualitative case study using structured interviews with six informants (two individuals with work experience, two fresh graduates who face obstacles due to lack of experience, and two fresh graduates without work experience who do not encounter such obstacles), as well as library research based on several relevant studies. Data validity was emphasized through source triangulation, iterative reading, peer debriefing, and member checking. Data analysis was conducted in two stages: deconstructive analysis, followed by elaborative analysis based on the Rawlsian principle of fair equality of opportunity. The results indicate that: (1) the mainstreaming of minimum work experience as a recruitment criterion reflects a form of logocentrism privileging a single dominant meaning—namely, work experience—as the center, which can create exclusion against certain groups of job-seekers by marginalizing other meanings or alternative possibilities of competence, such as learning ability, adaptability, work ethic, and others; (2) such logocentric practice also contradicts the Rawlsian principle of fair equality of opportunity, which emphasizes equal access and opportunity regardless of individuals' initial conditions, as it may create structural barriers for fresh graduates in accessing equal employment opportunities. The study concludes by recommending diversifying recruitment criteria and reorienting toward more inclusive practices, such as trial internships, probation, or management trainee programs.